Date seed coffee / Hafizah Hadran...[et al.] - Hadran, Hafizah; Ja’afar, Rabi’atul Ada’wiyah; Ibrahim, Muhammad Zabid; Mohd Darus, Nur Aimi; Badrul Hisham, Amirah Atiqah (2019)
Date Seed Coffee Pvt. Ltd. is a new start-up company that manufactures a new kind of coffee from date seeds. Date seed coffee is in powder based form and we sell it in 200g per can. Date seed extract are rich with antioxidant and anti-inflammatory effects. The date seed coffee can provide a calming, soothing, anti-inflammatory benefit to skin. Other than that, date seed promise to give an energizing, healthy and delicious coffee substitute.